Critical success factors in public-private partnerships (PPPs) on affordable housing schemes delivery in Tanzania: A qualitative study. Issue 2 (7th May 2019) - Kavishe, Neema; Chileshe, Nicholas
Abstract : Purpose: The purpose of this paper is to identify the critical success factors (CSFs) and key areas for improvement for public–private partnerships (PPP) in affordable housing schemes (AHS) projects, using Tanzania as a case study. Design/methodology/approach: Semi-structured interviews were conducted with 10 public and private sector practitioners in Tanzania. The collected data and the interview transcripts were analysed using the standard qualitative analysis technique of content analysis. Findings: The findings show the six most important CSFs as: a dedicated team of professionals to oversee the PPP projects, official and unofficial site visits and inspection, government support and guarantees, undertaking checks and balance from the design stage to construction stage, scrutiny of PPP project proposal and trust and integrity. The mapping of the CSFs across the PPP project lifecycle highlighted a higher incidence across the following phases: building ( n = 11), preparation ( n = 10) and operational ( n = 9). Practical implications: The identification of these CSFs would support PPP practitioners in successfully implementing PPP in AHS; besides, there is potential for their inclusion in the future development of the affordable housing PPP conceptual framework. Therefore, based on the identified CSFs, both the government and policy makers could use the findings as the basis for re-examining the existing PPP policy and regulations and reflecting on the existing situation with a view to improving the delivery of future PPP projects. Originality/value: This paper provides the first empirical study by applying direct content analysis to identify and understand the CSFs and key areas for improvement for PPPs in AHS within the Tanzanian housing sector. This is rather an under researched subject around CSFs for PPPs from developing countries such as Tanzania.